The Influence Of Organizational Culture And Physical Work Environment On The Work Effectiveness Of Public High School Teachers In Central Jakarta - Afriani Afriani; Matin Matin; Desi Rahmawati (Publikasi Indonesia, 2024)
The purpose of this study is to describe and describe comprehensively the influence of organizational culture and work environment on the work effectiveness of public high school teachers in Central Jakarta. This research was conducted at a public high school in Central Jakarta. This research method uses quantitative research survey methods, as for analyzing the data using path analysis. The path analysis technique in this study is to determine the causal relationship between variables or the direct influence of exogenous variables on endogenous variables. The endogenous variables in this study are work effectiveness, while the exogenous variables in this study are organizational culture and work environment. Data was collected through filling out a questionnaire. Based on the calculation results obtained path analysis: 1) organizational culture has a direct effect on the effectiveness of teachers' work with a path coefficient value of 0.728 and tcount of 15.510, meaning that organizational culture has a positive direct influence on the effectiveness of teachers' work, which can be accepted increasing. A good organizational culture increases the effectiveness of teachers' work. 2) the direct effect of the work environment on the effectiveness of the teacher's work, the path coefficient is 0.699 and tcount is 14,277. That is, the work environment has a direct effect on the effectiveness of the teacher's work. 3) Organizational culture has a direct positive effect on the work environment with a path coefficient value of 0.671 and tcount 13,218.